Patient Safety Centers in Brazil: A cross-sectional study (Research, Society and Development, 2021)
There has been a growing search focusing on offering a service of high quality and one strategy for the continuous improvement of the health service are Patient Safety Centers (PSC). This study aimed to analyze the composition and actions to patient safety improvement carried out by PSC in Brazilian hospitals from the perspective of health professionals who work in these instances. This is a study carried out using an online questionnaire. Large and medium-sized hospitals were selected, and their institutional e-mails were sought, inviting them to participate in the research. 107 hospitals from all regions of the country participated in the study, most of them philanthropic (46.9%) and medium complexity (51.6%). In 84.4%, PSCs have representativeness of team members, in an integrated manner (71.9%). However, there was a deficiency in the use of indicators and instruments for assessing the safety culture (62.5%). These results allowed an overview of the actual situation in which some PSCs are found in Brazilian territory. However, there is a need for improvement and the support of hospital leadership to strengthen the culture of patient safety.